The Pension Income of the Elderly: A Comparison between Belgium and the Netherlands - Gijs J. M. Dekkers (Luxembourg Income Study (LIS), 1998)
This article starts by discussing the two (semi-collective) layers of the pension system in the Netherlands separately. Then, the Belgian pension system will be discussed. Apart from the cost of the pension system (which will only be discussed very briefly), comparison of the pension systems required the comparison of the results of both systems i.e. the pension-income distribution in both countries. This will be done using the data of the Luxembourg Income Study or LIS. Lastly, new developments in the pension policy will be discussed.
Keywords: 330; Gesetzliche Rentenversicherung; Altersvorsorge; Vergleich; Belgien; Niederlande